Loss and Damage (L&D)—the economic and non-economic consequences of extreme weather events - CGIAR Climate Change Impact Platform (CGIAR Climate Change Impact Platform, 2024)
Welcome to the first video in CGIAR's Climate Impact Platform video series, where we explore the impacts of climate change on the agri-food sector. In this video, we dive into the concept of Loss and Damage (L&D) — the economic and non-economic consequences of extreme weather events like cyclones, droughts, and heatwaves.